CHILD MARRIAGE AND EDUCATION: STRATEGIES FOR INTERVENTION AND PREVENTION THROUGH LIBRARY RESEARCH AND CRITICAL PEDAGOGY - Rizqi, Sofan; Guefara, Rahmat Lutfi; Adawiyah, Siti Robiah; Roqib, Moh. (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Child marriage remains a significant global issue, particularly affecting young girls' education and future prospects. This study explores strategies for intervention and prevention of child marriage through a critical literature review, focusing on the role of education. Using a library research approach, the study highlights the intersectionality of child marriage with socioeconomic factors, gender inequality, and cultural traditions. The findings suggest that increased access to education and critical pedagogy can serve as effective tools for empowering girls and preventing early marriages. Moreover, the study emphasizes the importance of collaborative efforts between educational institutions, communities, and policymakers to create sustainable change.